2015
DOI: 10.1039/c5cp01980j
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the molecular and aggregated states of a drug molecule rutaecarpine using spectroscopy, microscopy, crystallography and computational studies

Abstract: The photophysical properties of a potential drug molecule rutaecarpine have been investigated in molecular as well as aggregated states. All systems have been characterized by various spectroscopic, microscopic and dynamic light scattering (DLS) techniques. The investigation has been carried out by keeping the fact in mind that hydrophobic organic molecules have a strong tendency to form aggregates in aqueous solution. A blue shift in the absorption spectrum of rutaecarpine has been observed for aggregates (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…The self-assembled aggregates based on ionic liquids (ILs) have attracted increasing attention during the past 10 years due to their extraordinary properties, such as negligible vapor pressure, low melting point, large electrochemical window, and thermal stability. , Ionic liquids with long alkyl chains are regarded as amphiphiles named as surface active ionic liquids (SAILs), which combine the properties of ILs and surfactants. SAILs can self-assemble into a rich variety of hierarchically complex architectures with controllable functions depending on the structure of SAILs and the composition of solution. Based on the designability of SAILs, it will be expected to achieve the functionalization of self-assembled aggregates by tailoring the structures of SAILs.…”
Section: Introductionmentioning
confidence: 99%
“…The self-assembled aggregates based on ionic liquids (ILs) have attracted increasing attention during the past 10 years due to their extraordinary properties, such as negligible vapor pressure, low melting point, large electrochemical window, and thermal stability. , Ionic liquids with long alkyl chains are regarded as amphiphiles named as surface active ionic liquids (SAILs), which combine the properties of ILs and surfactants. SAILs can self-assemble into a rich variety of hierarchically complex architectures with controllable functions depending on the structure of SAILs and the composition of solution. Based on the designability of SAILs, it will be expected to achieve the functionalization of self-assembled aggregates by tailoring the structures of SAILs.…”
Section: Introductionmentioning
confidence: 99%
“…[199] Thec o-assembly structures of worm-like micelles became slightly longer and more entangled (as shown by cryo-TEM) after 365 nm light irradiation, allowing to form as olution with ah igher viscosity.H owever,n o significant transformation of their self-assembled system was observed in studies by Yu et al [199] Self-assembly systems based on ionic liquids have attracted increasing attention due to their extraordinary properties,s uch as negligible vapor pressure,l ow melting point, and thermal stability. [200,201] Recently,b yi ntroducing photoresponsive units into an ionic liquid, e.g.,s tilbene,c innamate,a nd azobenzene,aseries of novel photoresponsive ionic liquid have been designed, [202][203][204][205] allowing for photocontrolled assembly transformations without co-assembly with other compounds. [206][207][208][209] It is noted that the photoresponsive surface active ionic liquid with azobenzene in the headgroup,i .e., amphiphile 16,s howed dualstimuli responsive and reversible transformations from vesicles to spherical micelles (Figure 19 a).…”
Section: Methodsmentioning
confidence: 99%
“…However, no significant transformation of their self‐assembled system was observed in studies by Yu et al [199] . Self‐assembly systems based on ionic liquids have attracted increasing attention due to their extraordinary properties, such as negligible vapor pressure, low melting point, and thermal stability [200, 201] . Recently, by introducing photoresponsive units into an ionic liquid, e.g., stilbene, cinnamate, and azobenzene, a series of novel photoresponsive ionic liquid have been designed, [202–205] allowing for photocontrolled assembly transformations without co‐assembly with other compounds [206–209] .…”
Section: Functional Supramolecular Self‐assembly Of Photoresponsive Molecular Amphiphiles In Solutionmentioning
confidence: 99%
“…This is the first step for identifying ILs as potential carrier agents in drug delivery devices. Accordingly, a large number of reports comprising ILs as solvents to be employed in the development of promising drug delivery strategies have been published in the literature, namely by IL-based micelles [ 79 , 80 , 81 , 82 ], microemulsions [ 12 , 48 , 83 , 84 , 85 ], nanoparticles [ 86 , 87 , 88 , 89 , 90 ], functionalized silica [ 91 , 92 , 93 , 94 ], and iongels [ 95 , 96 , 97 , 98 ]. These possibilities stand out as the most relevant examples for delivery approaches with ILs, as summarized in Figure 4 .…”
Section: Il-based Drug Delivery Systemsmentioning
confidence: 99%
“…The results gathered revealed a high potential of SAILs to develop more efficient drug delivery processes. In the same line, Dandpat et al [ 81 ] investigated the aggregation and dissociation behavior of hydrophobic drugs, namely rutaecarpine, in the presence of [C 12 C 1 im]Br by using spectroscopic, microscopic, and crystallographic analysis. The authors found that drug aggregation decreases in solution with the gradual addition of [C 12 C 1 im]Br.…”
Section: Il-based Drug Delivery Systemsmentioning
confidence: 99%